The liver-brain axis under the influence of chronic Opisthorchis felineus infection combined with prolonged alcoholization - D. F. Avgustinovich; I. V. Chadaeva; A. V. Kizimenko; A. V. Kovner; D. V. Bazovkina; D. V. Ponomarev; V. I. Evseenko; V. A. Naprimerov; M. N. Lvova (Вавиловский журнал генетики и селекции, 2025)
Our purpose was to model a combination of a prolonged consumption of ethanol with Opisthorchis felineus infection in mice. Four groups of C57BL/6 mice were compiled: OF, mice infected with O. felineus for 6 months; Eth, mice consuming 20 % ethanol; Eth+OF, mice subjected to both adverse factors; and CON, control mice not exposed to these factors. In the experimental mice, especially in Eth+OF, each treatment caused well-pronounced periductal and cholangio fibrosis, proliferation of bile ducts, and enlargement of areas of inflammatory infiltration in the liver parenchyma. Simultaneously with liver disintegration, the infectious factor caused – in the frontal cerebral cortex – the growth of pericellular edema (OF mice), which was attenuated by the administration of ethanol (Eth+OF mice). Changes in the levels of some proteins (Iba1, IL-1β, IL-6, and TNF) and in mRNA expression of genes Aif1, Il1b, Il6, and Tnf were found in the hippocampus and especially in the frontal cortex, implying region-specific neuroinflammation. Behavioral testing of mice showed that ethanol consumption influenced the behavior of Eth and Eth+OF mice in the forced swimming test and their startle reflex. In the open field test, more pronounced changes were observed in OF mice. In mice of all three experimental groups, especially in OF mice, a disturbance in the sense of smell was detected (fresh peppermint leaves). The results may reflect an abnormality of regulatory mechanisms of the central nervous system as a consequence of systemic inflammation under the combined action of prolonged alcohol consumption and helminth infection.